Character Education Transformation in Elementary Schools in the Society 5.0 Era: A Study of the Seven Habits of Great Indonesian Children (KAIH) - Iklil majid Mudhoffar; Farah Nurin Shabrina; Sofwan Roif Ubaidillah; Abd Muhith; Suparwoto Sapto Wahono (Journal of Educational Sciences, 2026)
The development of digital technology in the Society 5.0 era has significantly influenced changes in the character of elementary school students, leading to issues such as declining discipline, empathy, and social responsibility. This condition underscores the need for character education that is relevant to contemporary societal developments. This study aims to examine the contribution of the Seven Habits of Great Indonesian Children (7 KAIH) program to strengthening students’ character. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation at SDN Kaliwates 01. The findings revealed that implementing the seven habits waking up early, praying, exercising regularly, cultivating a love of learning, consuming healthy and nutritious food, participating in community life, and going to bed early positively influenced students’ character development. Students demonstrated improved discipline, responsibility, active engagement in learning, and greater social awareness. In addition, improvements were observed in students’ physical well-being and readiness to learn. The program’s success was supported by strong collaboration between the school and parents in guiding and consistently monitoring the implementation of these habits. Therefore, the 7 KAIH program contributes positively to strengthening character education among elementary school students and serves as a relevant strategy for addressing educational challenges in the digital era.